PERAN MEDIASI MOTIVASI KERJA DALAM PENGARUH KOMPENSASI TERHADAP SEMANGAT KERJA - Iswara, Windu; Subudi, Made (E-Jurnal Manajemen, 2017)
Compensation factors and motivational play an important role in increasing spirit at work. This study was conducted to determine the effect of compensation on spirit at work at and to determine the motivational role in mediating the influence of compensation on employee morale. The study was conducted on employees Unagi Handicraft & Painting by the number of respondents as many as 40 employees. The number of respondents is determined using saturation sampling technique. The data collection is done by distributing questionnaires using a 5-point Likert scale to measure 11 indicators. Data analysis technique used is path analysis. The test results compensation positive and significant impact on spirit at work, compensation positive and significant impact on motivation and motivation positive and significant impact on spirit at work. The limitation of this study is the location of this research will be in the scope of the industry in Unagi Handicraft & Painting so the results of this study can not explain the circumstances of the other industry besides Unagi Handicraft & Painting .
Keywords: compensation, motivation, spirit at work